Ascorbic Acid Alleviates Water Stress in Young Peach Trees and Improves Their Performance after Rewatering - Penella, Consuelo; Calatayud, Ángeles; Melgar, Juan C. (Frontiers in Plant Science, 2017)
Exogenous application of biochemicals has been found to improve water stress tolerance in herbaceous crops but there are limited studies on deciduous fruit trees. The goal of this research was to study if ascorbic acid applications could improve physiological mechanisms associated with water stress tolerance in young fruit trees. Ascorbic acid was foliarly applied at a concentration of 250 ppm to water-stressed and well-watered peach trees (control) of two cultivars (‘Scarletprince’ and ‘CaroTiger’). Trees received either one or two applications, and one week after the second application all trees were rewatered to field capacity. Upon rewatering, CO2 assimilation and stomatal conductance of water-stressed ‘Scarletprince’ trees sprayed with ascorbic acid (one or two applications) were similar to those of well-irrigated trees, but water-stressed trees that had not received ascorbic acid did not recover photosynthetical functions. Also, water status in sprayed water-stressed ‘Scarletprince’ trees was improved to values similar to control trees. On the other hand, water-stressed ‘CaroTiger’ trees needed two applications of ascorbic acid to reach values of CO2 assimilation similar to control trees but these applications did not improve their water status. In general terms, different response mechanisms to cope with water stress in presence of ascorbic acid were found in each cultivar, with ‘Scarletprince’ trees preferentially using proline as compatible solute and ‘CaroTiger’ trees relying on stomatal regulation. The application of ascorbic acid reduced cell membrane damage and increased catalase activity in water-stressed trees of both cultivars. These results suggest that foliar applications of ascorbic acid could be used as a management practice for improving water stress tolerance of young trees under suboptimal water regimes.